PERANAN ASAS ITIKAD BAIK DALAM MEWUJUDKAN KEADILAN PARA PIHAK DALAM PERJANJIAN - Anita Sinaga, Niru (Feb Universitas Dirgantara Marsekal Suryadarma, 2018)
Today's business is growing, both small, medium and upper scale. Talking about business is inseparable from the so-called agreement. Almost every day we make arrangements. It is therefore necessary to understand important matters relating to a treaty, such as: What is the agreement, the terms of the agreement, the principles of the agreement, the object of the agreement, the terms of the agreement, the form of the agreement, the parties involved, the right and the obligations of the parties, the structure and the anatomy of the agreement, the settlement of disputes and the termination of the agreement. In general, the agreement is: The parties' agreement on something that gives birth to a legal relationship, creates rights and obligations, if not executed as promised there will be sanctions. The purpose of making the treaty is similar to the legal objectives in general, namely the creation of justice, order, and legal certainty. In order for what is promised to run well then required a regulating rule, called the law of agreement. But in practice it is often not in accordance with the objective of the agreement that is to provide protection for the parties, the creation of justice, order, and legal certainty. The discussion in this study is to discuss about: What things should be considered or fulfilled to realize the achievement of the purpose of an agreement and How the role of good faith principle in realizing justice for the parties. The method used is normative juridical. In the event of a dispute concerning the agreement, it should be settled with due regard to the principles contained in the treaty law, especially the principle of good faith. Keywords: Agreement, Good Faith and Justice Principle